Competing forms in conditional constructions in the diachrony of Portuguese - Brocardo, Maria Teresa (2019)
In Portuguese past stages, both simple pluperfect (MPS) and conditional (COND) forms occurred in the apodosis of conditional constructions. In this study I investigate the ‘competition’ (cf., a.o., Berg, 2014), in the mentioned constructions, of these two verbal paradigms, in data retrieved from late 15th to early 17th century’s textual sources. In most cases, the interpretation of the constructions contrasts: with MPS forms the constructions have a counterfactual reading, while constructions with COND forms are interpretable as hypothetical, thus evidencing the persistence, in modal uses, of the distinct tense values of these paradigms. Some ‘critical’ examples, however, appear to show that, in some contexts, the MPS is compatible with a non-counterfactual interpretation and also that the COND could have a counterfactual reading. I discuss the various conditioning factors which may have contributed to the convergence, and thus the competition, in conditional constructions, of the MPS and the COND, and the factors which may have determined the obsolescence of the modal uses of the MPS in the diachrony of Portuguese.